Metrics and Statistical Modeling of Ambient Noise with Emphasis on Calving Noise from a West Greenland Fjord - Farrell, Dara Mary (My University, 2019)
This dissertation is a compilation of explorations of various methods related to mapping, methods and modeling. These methods are useful in the study of acoustic data. The exploration of data in this work from a Greenland fjord represents most (although not all) of these methods and therefore influences the title of this work. In this work, the background noise environment in a glacial fjord was measured and the data were analyzed. The work explores the utility of spectral probability density (SPD) in evaluating background noise characteristics in the frequency domain, models probability density functions (PDFs) of spectral levels and introduces a parameter \(\sigma_T\) that quantifies the character of noise in frequency bands of interest; this work demonstrates that the empirical PDFs used in the SPD can be replaced by analytical PDFs if the spectral estimates can be considered to be exponential random variables. It also explores the utility of k-medoids clustering as a pre-sorting method to inform the selection of features on which to base the training of more complex algorithms.
Thesis (Ph.D.)--University of Washington, 2019
Keywords: acoustics; calving; clustering; Florida; Greenland; shallow water; Acoustics; Mechanical engineering; Statistics; Mechanical engineering